Prarancangan Pabrik Mtbe (Metil Tertiari Butil Eter) Dari Metanol Dengan Disain Alat Utama Reaktor MTBE (R-101) - Pranoto, Monica Kartiningtyas; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
There are more motorized vehicles in Indonesia in line with the increasing demand for fuel. This development will have a negative impact, environmental pollution so MTBE is a substances with a lower risk and environmentally friendly are chosen. The target market of this factory is to meet the need for MTBE in Indonesia and to export it to the Asia Pacific region. MTBE production process is carried out by reacting methanol with isobuten with a capacity is 280,000 tons/year. The MTBE reactor serves as a place for reacting methanoland isobuten to produce MTBE. The reactor is fixed bed multi tube type which has 109 tubes with Torisperical flanged dished head. Reactor operating temperature is 60ºC, pressure is 6 bar and using Amberlyst 15 as catalyst. The height of the reactor is 26.3 ft and diameter is 4.5 ft. The reaction is exothermic, so the principle of the reactor is like a shell and tube heat exchanger with cooling water flow of 1,070,054 lb/hour. The value of FixedCapital Investment is $ 39,009,534. The value of the Working Capital Investment is obtained 15% of the Total Capital Investment (TCI) or worth $ 6,884,035 so that the TCI is $ 45,893,569. The total production cost is $ 349,777,652 so that it will generate a grossprofit as $ 220,011,513 after deducting 35% tax. ROI after tax is 88%, BEP is 50% and Pay out time for 1 year with a Shut Down Point is 0.23%. This factory has an IRR that is 22.76% which is greater than the RRR of a bank which is 22.55%, then the value of NPV is $ 90,140,564 which is greater than the TCI. From these two factors, it can be concluded that the MTBE plant is feasible to build.Keyword: Isobutene, Methanol, methyl tert butyl ether, reactor fixed bed multi tube